Heat Transfer and Thermal Expansion of Coefficient EP -(MWCNT/x-TiO2)Nanocomposites - Dhilal Amer Sabar; Fadhil K. Farhan (Journal of Engineering, 2018)
The thermal properties (thermal transfer and thermal expansion coefficient) of the enhanced epoxy resin (MWCNT / x-TiO2) were studied by weight ratios with the values (0%, 3%, 5%, 7% and 10%) and a constant ratio of 3% of MWCNT. The ultrasonic technology was used to prepare the neat and composites which were then poured into Teflon molds according to standard conditions. Thermo-analyzer sensor technology was used to measure thermal transfer (thermal conductivity, thermal flow, thermal diffusion, thermal energy and heat resistance). The thermal conductivity, flow, and thermal conductivity values were increased sequentially by increasing the weight ratio of the filler while the results of stored energy values and thermal resistance decreased by increasing the percentage of salts. The thermal mechanical analysis was used to measure thermal expansion and elasticity coefficient. The scanning electron microscopy was used to interpret the results of thermal analysis and distribution of the nanoparticle within the polymer matrix.